Impact of climate change on coffee production in the north east Peruvian - Hurtado, Roxana (2022)
This research was conducted with the purpose of determining the impacts of climate change and its economic impact on coffee farms, and in this way evaluate the vulnerability of coffee crop production by conducting a literature review of the impact of climate change on coffee production in the North East of Peru. This study was of quantitative approach, of descriptive level. The study area was constituted by 3 regions (Amazon, Cajamarca and San Martin). It is concluded that the main impacts of the climatic change, affects in technical, socioeconomic, and environmental aspects, the studies carried out on the influence of the climatic change, was evidenced in the increase of plagues and diseases that affect the coffee. On the basis of the mentioned, a substantial increase in economic losses of the production is noticed, the economic incidence in coffee farms in the Peruvian Northeast through time the greater production was reflected in the region San Martin, Cajamarca and Amazon. The price in the 3 regions oscillates between 4, 5, 6 and 7 soles approximately, as for the decrease of the production it was due to the changes of the climatic factors (phenomenon of the child in 2012 and 2016).